2021
DOI: 10.1111/epic.12065
|View full text |Cite
|
Sign up to set email alerts
|

Anticipating Connectivity in (UX) Design Practices: Reframing Challenges by Introducing Theory Cards

Abstract: This paper presents a design anthropological study with User Experience design departments from five large companies in Denmark, ranging from manufacturers of medical equipment through toys to control systems for industrial infrastructures We explore the challenges they face as products, services, and user research are increasingly connected. Our research shows that current methods, development processes, and organizational structures do not sufficiently support User Experience design teams in dealing with eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
(14 reference statements)
0
6
0
Order By: Relevance
“…These changes infiltrate the products themselves, their use and implementation, design processes, organizational cultures and structures, and the human-human and human-object relations implicated at all of these levels. In an earlier paper (Kjaersgaard et al 2021), we describe these findings and our first design research experiment aimed at solving some of the issues we identified. By the end of that experiment, we had come to the conclusion that what design practitioners needed most, in order to remain effective and relevant in a fast-changing field, was fresh perspectives.…”
Section: From Perspectives To Ways Of Seeingmentioning
confidence: 96%
See 3 more Smart Citations
“…These changes infiltrate the products themselves, their use and implementation, design processes, organizational cultures and structures, and the human-human and human-object relations implicated at all of these levels. In an earlier paper (Kjaersgaard et al 2021), we describe these findings and our first design research experiment aimed at solving some of the issues we identified. By the end of that experiment, we had come to the conclusion that what design practitioners needed most, in order to remain effective and relevant in a fast-changing field, was fresh perspectives.…”
Section: From Perspectives To Ways Of Seeingmentioning
confidence: 96%
“…In 2020, some of our collaborators contacted us, feeling that they had exhausted their userresearch methods without drawing forth particularly new or relevant insights. To investigate this frustration, we initiated the project New Challenges in Interaction Design, which has involved several stages of studying practitioners and the emerging issues they face in their everyday work (Kjaersgaard et al 2021).…”
Section: From Perspectives To Ways Of Seeingmentioning
confidence: 99%
See 2 more Smart Citations
“…With increasing digitalization, design researchers and designers in the industry are struggling to take into account the effects that interactive products have on users and their lives. In a study of UX practices in manufacturing companies, Kjaersgaard et al (2021) argue that this is not simply a problem of finding better methods; rather, it is a more fundamental question of theoretical perspectives. To help practitioners gain broader perspectives, we have started experimenting with theory instruments-tangible objects that work as conversation starters to challenge the taken-for-granted assumptions about people and technologies.…”
Section: Introductionmentioning
confidence: 99%